Time Efficiency and Ergonomic Assessment of a Robotic Wheelchair Transfer System - Shantanu A. Satpute; Kaylee J. Uribe; Oluwatofunmi O. Olaore; Minori Iizuka; Ian C. McCumber Gandara; William J. Schoy; Rutuja A. Kulkarni; Rosemarie Cooper; Alicia M. Koontz; Owen Flaugh; Rory A. Cooper (Sensors)
Background: Caregivers experience high rates of occupational injuries, especially during wheelchair transfers, which often result in back pain and musculoskeletal disorders due to the physical demands of lifting and repositioning. While mechanical floor lifts, the current standard, reduce back strain, they are time-consuming and require handling techniques that subject caregivers to prolonged and repeated non-neutral trunk postures, increasing the risk of long-term back injuries. Aims: The aim was to assess the time efficiency and ergonomics of the powered personal transfer system (PPTS), a robotic transfer device designed for bed-to/from-wheelchair transfers. Methods: We evaluated transfers with the PPTS and mechanical lift with eight able-bodied participants who assisted with transfers between a bed and a wheelchair. Inertial measurement units (IMUs) were placed on participants to track their motion and assess trunk joint angles during transfers. Results: The PPTS significantly reduced the transfer time (144.31 s vs. 525.82 s, p < 0.001) and required significantly less range of motion for trunk flexion (p < 0.001), lateral bending (p = 0.008), and axial rotation (p = 0.001), all of which have been associated with back injuries. Additionally, the PPTS significantly reduced the time caregivers spent in non-neutral trunk postures, potentially lowering injury risks. Conclusions: These findings suggest that the PPTS improves transfer efficiency and caregiver safety, offering a promising alternative to the current standard of care for wheelchair-to/from-bed transfers.